Analysis of the recovery determinant factors of COVID-19 sufferes - Diadjeng Setya Wardani; Arifin Syamsul (International Journal of Public Health Science (IJPHS), 2021)
The main factor that affects the recovery of people with COVID-19 is immunity. To increase immunity, sufferers of COVID-19 must be able to regulate their bodies and psychological conditions so they don't get stressed because they reduce immunity very quickly. The purpose of this study was to determine the determinants that affect the recovery of COVID-19 sufferers. This research employed a cross-sectional design. The respondent was 30 patients who recovered from COVID-19. The data collection instruments used questionnaires and interview sheets. Data analysis used Fisher's exact test (a=5%) and calculated the prevalence ratio to determine the determinant factors. The results showed that age (p-value 0.034, PR=0.667) and patient education (p-value 0.023, PR=0.600) showed a significant effect, while gender (p-value 0.687, PR=0.78), occupation (p-value 0.253, PR=0.333), income (p-value 0.520, PR=0.895), and patient origin (p-value 0.393, PR=1.118) did not show a significant effect. The determinants that affect the recovery of COVID-19 sufferers are age and education of the sufferer; while gender, occupation, income, and origin do not have a significant effect on the recovery of COVID-19 sufferers.